Human Endogenous Retrovirus K (HML-2) in Health and Disease - Xue, Bei; Sechi, Leonardo A.; Kelvin, David J. (Frontiers in Microbiology, 2020)
Human endogenous retroviruses (HERVs) are derived from exogenous retrovirus infections in the evolution of primates and account for about 8% of the human genome. They were considered as silent passengers within our genomes for a long time; however, reactivation of HERVs has been associated with tumors and autoimmune diseases, especially the HERV-K (HML-2) family, the most recent integration groups with the least number of mutations and the most biologically active to encode functional retroviral proteins and produce retrovirus-like particles. Increasing studies are committed to determining the potential role of HERV-K (HML-2) in pathogenicity. Although there is still no evidence for HERV-K (HML-2) as a direct cause of diseases, aberrant expression profiles of the HERV-K (HML-2) transcripts and their regulatory function to their proximal host-genes were identified in different diseases. In this review, we summarized the advances between HERV-K (HML-2) and diseases to provide basis for further studies on the causal relationship between HERV-K (HML-2) and diseases. We recommended more attention to polymorphic integrated HERV-K (HML-2) loci which could be genetic causative factors and be associated with inter-individual differences in tumorigenesis and autoimmune diseases.